Um estudo abrangente dos frutos de Moringa oleifera (Lam) e sua relevância no enriquecimento de massas alimentícias para melhoramento nutricional - Leão, Marcos Venânces de Souza (2022)
The species Moringa oleifera Lam. It has high levels of nutritionally relevant constituents, both in its leaves, seeds and fruits, which gives it high potential as an adjuvant in the elaboration of nutritionally enriched food products. According to Brazilian legislation, pasta is the product obtained from the mixing and kneading of wheat flour or semolina with water, and the addition or not of other substances allowed in human consumption. The main objectives of the present work were to verify the toxicity of moringa fruit flour, to evaluate the technological aspects of wheat flour and mixed flours, to develop enriched pasta (MAE's) with improved nutritional value and incorporation of bioactive compounds. The samples were analyzed for toxicity, physical-chemical parameters, rheological and technological properties. The results showed that no cytotoxicity was observed in human neutrophil culture and no indicators of acute toxicity for the microcrustacean species Artemia salina. Important properties regarding the technological aspect of the doughs were changed with the addition of moringa pod flour (FVM) to wheat flour, notably the parameters of color, water activity, humidity, falling number, damaged starch, gluten contents (wet, dry and index), water absorption, stability, toughness and extensibility. It was observed that the formulations added with FVM showed an increase in the mineral fraction, dietary fibers and in the concentration of total phenolic compounds, flavonoids, and β-carotene and lycopene carotenoids compared to the control sample. The technological quality tests showed significant differences (p<0.05) between all samples, with reduced cooking time, solid loss and weight and volume increase for the doughs added with FVM, in relation to the control. It is concluded that FVM is safe regarding the toxicological aspect and that its addition in the percentages of 15% and 20% in substitution of wheat flour, conferred nutritional gain to the products, added bioactive compounds to the pasta, when compared to conventional products and although it has given significant changes in the technological properties, it has not made it impossible to produce these products on a laboratory scale